Stress among Healthcare Workers during COVID19 Pandemic: Crucial Elements for Hospital Management / Salmi Razali ... [et.al.]. - Razali, Salmi; Ab Rahman, Norhayati; Abdullah, Najib; Azhar, Nur Amira; Yaacob, Siti Sara; Putit, Lennora (Universiti Teknologi MARA Cawangan Sarawak, 2022)
The COVID-19 outbreak has impacted global mental health and wellbeing those severely affected are the healthcare workers (HCWs). Despite the overwhelming consequences, there is sparse knowledge on subjective opinions of HCWs on factors contributing to their stress. This study aimed to explore the opinions of HCWs on factors contributing to their psychological distress. We analysed thematically secondary data of the opinions and suggestions of HCWs, which were retrieved from the computerized mental health monitoring system and online Psychosocial First Aid of the main admitting hospital for COVID-19 in Malaysia and its related healthcare facilities during the second wave of the pandemic.